Production and consumption of fruit and berry crops in the Bryansk region - O. N. Korosteleva; T. A. Kazimirova (Путеводитель предпринимателя, 2020)
The paper presents the main indicators gross harvest, yield of fruit and berry crops in the Bryansk region, analyzed the volume of consumption and production.